Cardiac Resynchronization Therapy and Risk of Recurrent Hospitalizations in Patients Without Left Bundle Branch Block: The Long-Term Multicenter Automatic Defibrillator Implantation Trial With Cardiac Resynchronization Therapy. (July 2020) - Vidula, Himabindu; Lee, Elizabeth; McNitt, Scott; Polonsky, Bronislava; Aktas, Mehmet; Rosero, Spencer; Younis, Arwa; Solomon, Scott D.; Zareba, Wojciech; Kutyifa, Valentina; Goldenberg, Ilan
Abstract : Background: Mild heart failure (HF) patients without left bundle branch block (LBBB) did not derive a significant reduction in risk of a HF event/death in the MADIT-CRT trial (Multicenter Automatic Defibrillator Implantation Trial With Cardiac Resynchronization Therapy). However, the efficacy of CRT with a defibrillator (CRT-D) may be modified after the development of the first hospitalization for HF (HHF). We aimed to study the effect of CRT-D on long-term risk of recurrent HHF in patients without LBBB in MADIT-CRT. Methods: Data on recurring HHF were collected for 1818 subjects. The CRT-D versus implantable cardioverter-defibrillator-only risk for first and subsequent HHF was assessed by QRS morphology in on-treatment analysis using Cox proportional hazards regression modeling. Results: During long-term follow-up, 412 patients had ≥1 HHF and 333 had ≥2 HHF. Multivariate analysis revealed that in LBBB patients, CRT-D, compared with implantable cardioverter-defibrillator, was associated with a significant reduction in risk of first and subsequent HHF (first: hazard ratio, 0.41 [95% CI, 0.31–0.54], P <0.001; subsequent: hazard ratio, 0.45 [95% CI, 0.29–0.70], P <0.001). Among patients without LBBB, the benefit of CRT-D was nonsignificant for the first HHF (hazard ratio, 0.96; P =0.808). However, after occurrence of a first HHF, CRT-D therapy was associated with a pronounced 44% reduction in risk of subsequent HHF (hazard ratio, 0.56 [95% CI, 0.32–0.97], P =0.039). Patients without LBBB with ≥1 HHF during the first year of follow-up demonstrated increasing dyssynchrony at 1 year compared with those who had no HHF ( P =0.016). Conclusions: In MADIT-CRT, we show a beneficial effect of CRT-D in patients without LBBB subsequent to development of a first HHF, possibly due to increased dyssynchrony associated with HF progression. Registration: URL: https://www.clinicaltrials.gov . Unique identifier: NCT00180271, NCT01294449, and NCT02060110. Abstract : Supplemental Digital Content is available in the text.